THE EFFECT OF PRODUCT DESIGN, PRICE, AND PROMOTION ON IMPULSIVE BUYING OF THE ORIGINOTE PRODUCTS IN TIKTOK SHOP - Sri Sauzi Amalia; Muchsin; Mohd. Heikal; Sapna Biby (RADJA PUBLIKA, 2025)
The purpose of this study is to determine and analyze the influence of product design, price, and promotion on impulsive buying of The Originote products in TikTok Shop. The population in this study were active students of the Faculty of Economics and Business, Malikussaleh University. The sample in this study were students who had purchased The Originote products in TikTok Shop. Respondents used in this study amounted to 112 people. Primary data in this study were collected by means of questionnaires or distributing questionnaires and secondary data obtained from journals and internet media. The data analysis techniques used were multiple linear regression analysis methods, classical assumption tests, validity and reliability tests, research hypothesis tests, and coefficients of determination using the SPSS 26 program. This type of research is quantitative research. The results showed that partially product design (X1), price (X2), and promotion (X3) had a positive and significant effect on impulsive buying. Product design is the most dominant variable influencing impulsive buying of The Originote products in TikTok Shop among students of Economics and Business, Malikussaleh University. The adjusted R square value is 21.5% while the remaining 78.5% can be explained by other variables not examined in this study.